Aktivitas Farmakologis Murbei Putih (Morus Alba): Kajian Pustaka - Ihsani Putri Henda Muharam; Nurul Romadhona (UNISBA Press, 2022)
Abstract. Plant extracts are rich in phytochemicals, one of which comes from the Morus genus of the Moraceae family, also known as mulberry. The mulberry plant has more than 150 species including the white mulberry (Morus alba), the black mulberry (Morus nigra), and the red mulberry (Morus rubra). The white mulberry leaf plant can be found in several regions of Africa, South America, North America, Northwest South America, East Asia, West Asia, and Southeast Asia including Indonesia. White mulberry is a plant that has various pharmacological activities so it is commonly used as traditional medicine. Traditional medicine itself in the community is considered to have no side effects. White mulberry has often been used as traditional medicine in China for hundreds of years. White mulberry in Indonesia is a plant that is often used as feed for silkworms. One of the areas in Indonesia that contain white mulberry is in the ex-situ conservation of the Bogor Botanical Gardens. White mulberry contains a fair amount of protein, carbohydrates, fat, fiber, minerals, and several precursors of vitamins. Various kinds of the content contained in white mulberry causes white mulberry to have various benefits in the pharmacological world. The writing of this article is a literature review that aims to provide information about the activity of the white mulberry plant (Morus alba). Abstrak. Ekstrak tumbuhan yang kaya akan fitokimia salah satunya berasal dari Genus Morus dari Family Moraceae atau dikenal dengan murbei. Tanaman murbei memiliki spesies lebih dari 150 diantaranya murbei putih (Morus alba), murbei hitam (Morus nigra), dan murbei merah (Morus rubra). Tanaman daun murbei putih tersebut dapat ditemukan di beberapa wilayah Afrika, Amerika Selatan, Amerika Utara, Barat Laut Amerika Selatan, Asia Timur, Asia Barat dan Asia Tenggara termasuk negara Indonesia. Murbei putih merupakan salah satu tanaman yang memiliki berbagai aktivitas farmakologis sehingga biasa digunakan menjadi pengobatan tradisional. Obat tradisional sendiri di kalangan masyarakat dianggap tidak memiliki efek samping. Murbei putih sering sudah dijadikan pengobatan tradisional di Cina selama ratusan tahun ke belakang. Murbei putih di Indonesia merupakan tumbuhan yang sering digunakan sebagai pakan ulat sutera. Wilayah di Indonesia yang terdapat murbei putih salah satunya berada di Konservasi ex situ Kebun Raya Bogor. Murbei putih mengandung cukup banyak protein, karbohidrat, lemak, serat, mineral, dan beberapa prekursor dari vitamin. Berbagai macam kandungan yang terdapat di murbei putih menyebabkan murbei putih memiliki berbagai manfaat dalam dunia farmakologis. Penulisan artikel ini merupakan suatu kajian pustaka yang bertujuan untuk memberikan informasi tentang aktivitas farmakologis dari tanaman murbei putih (Morus alba).